2021
DOI: 10.3389/fpsyt.2021.634418
|View full text |Cite
|
Sign up to set email alerts
|

A Research Domain Criteria Approach to Gambling Disorder and Behavioral Addictions: Decision-Making, Response Inhibition, and the Role of Cannabidiol

Abstract: Gambling Disorder (GD) has been recently re-classified in the DSM-5 under the “substance-related and addictive disorders,” in light of its genetic, endophenotypic, and phenotypic resemblances to substance dependence. Diminished control is a core defining concept of psychoactive substance dependence or addiction and has given rise to the concept of “behavioral” addictions, which are syndromes analogous to substance addiction, but with a behavioral focus other than ingestion of a psychoactive substance. The main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 76 publications
0
1
0
Order By: Relevance
“…Y. Qian et al [42] found that cannabidiol reduced cocaine withdrawal symptoms and craving, and improved cognitive function and mood in mice. The possibility of using cannabidiol and its analogues as an alternative treatment for pain and prevention of opioid abuse in rats [43], gambling and behavioural addiction [44] has also been identified. A recent double-blind, randomised study by R.M.…”
Section: Legal Status Prevalence and Potential Impacts Of Cannabismentioning
confidence: 99%
“…Y. Qian et al [42] found that cannabidiol reduced cocaine withdrawal symptoms and craving, and improved cognitive function and mood in mice. The possibility of using cannabidiol and its analogues as an alternative treatment for pain and prevention of opioid abuse in rats [43], gambling and behavioural addiction [44] has also been identified. A recent double-blind, randomised study by R.M.…”
Section: Legal Status Prevalence and Potential Impacts Of Cannabismentioning
confidence: 99%